A novel high temperature retarder applied to a long cementing interval. Issue 17 (3rd February 2016) - Lu, Ya; Li, Ming; Guo, Zihan; Guo, Xiaoyang
Abstract : A retarder comprised of sodium styrene sulfonate, itaconic acid and hydroxyethyl methacrylate was synthesized by aqueous free radical copolymerization, which can be applied to a long cementing interval. Abstract : A polymer comprised of sodium styrene sulfonate (SSS), itaconic acid (IA) and hydroxyethyl methacrylate (HEMA) was synthesized by aqueous free radical copolymerization and tested as high temperature performing retarder in oil well cement, which was characterized by gel permeation chromatography (GPC), infrared spectroscopy (IR), and thermal gravimetric analysis (TG). The optimum reaction conditions of polymerization were obtained: a mass ratio of SSS/IA/HEMA (PSIH) 9 : 3 : 1, initiator 2%, a reaction temperature of 60 °C, a reaction time of 5 h; characterization evidenced the PSIH had a certain molecular weight and excellent thermal resistance. Performance evaluation showed that the PSIH had good retarding properties at 150 °C, and demonstrated rapid development of compressive strength at 30 °C, providing a strong technical support for complex deep well cementing. Moreover, the retarding mechanism of PSIH was found, through XRD and SEM, to rely on adsorption onto the surface of the cement and chelation of calcium.